Influência de nanocristais de celulose sobre as propriedades de filmes de gelatina de resíduos de tilápia - Santos, Talita Macedo dos (2012)
Currently the studies about biodegradable materials and waste recovery are increasing, due to need to preserve natural resources and other issues related to sustainability. The objective of this work is to develop biodegradable films from tilapia waste gelatin and cellulose nanocrystals (CN). The formulation of the film was made with 9.6% fish gelatin, glycerol 25% (on dry basis) and varying the amount of nanocrystals from linter pulp at concentrations of 0, 5, 10 and 15% (on a dry basis) and the use of ultrasonic treatment (US) in the preparation of films. The films were obtained by casting and characterized with respect to water vapor permeability (WVP), mechanical properties (tensile strength, elongation and elastic modulus), thermal properties (DSC), optical properties, color stability, morphology (SEM) and hydrophilicity by contact angle. The obtained films are presented in good shape, homogeneous and manageable, with good transparency and moisture content between 12.5 and 20.7%, which decreased significantly with adding CN. Cellulose nanocrystals were effective in reducing the permeability, substantially decreasing WVP with use of 10% CN and US, and 15% of NC with US and without US. The addition of CN increased tensile strength from 5% CN and with a small decrease in concentration of 15%. The elastic modulus increased at 15% with US. There was no significant effect with the addition of NC and use of US at elongation of films and no effects in opacity of films. The use of ultrasound has improved barrier to water vapor and elastic modulus, and it did not has significant influence on the properties of tensile strength, elongation and opacity. The images obtained by scanning electron microscopy showed structures originating from gelatin, possibly by presence of minerals or crystal structures of collagen in the process of obtaining gelatin or films, and processes with storage time. The DSC analysis showed possible phenomena of gelatin melting or other thermal processes simultaneously in the first cycle, and thermal processes in the second cycle, which can be associated with glass transition of gelatin. These events were not influenced significantly by CN content and use of US, but were heavily influenced by storage time of films. These showed little color intensity, which was further enhanced by the amount of CN and did not vary significantly with time, indicating that colors of the films were stable. Contact angle analysis have shown that CN did not decrease the hidrofilicity of films. The best film obtained for application to food products was 10% with NC and use of ultrasound due to better barrier to water, improved mechanical properties and the same transparency.